Social networks - Joan de Martí; Yves Zenou (Institute for the Study of Labor (IZA), 2009)
We survey the literature on social networks by putting together the economics, sociological and physics/applied mathematics approaches, showing their similarities and differences. We expose, in particular, the two main ways of modeling network formation. While the physics/applied mathematics approach is capable of reproducing most observed networks, it does not explain why they emerge. On the contrary, the economics approach is very precise in explaining why networks emerge but does a poor job in matching real-world networks. We also analyze behaviors on networks, which take networks as given and focus on the impact of their structure on individuals' outcomes. Using a game-theoretical framework, we then compare the results with those obtained in sociology.
Keywords: A14; C72; D85; Z13; 330; Random graph; game theory; centrality measures; network formation; weak and strong ties; Soziales Netzwerk; Graphentheorie; Spieltheorie; Netzwerk; Wirtschaftsmodell; Theorie